The Impact of Erosion of Trust among Educators on the Decline of Key Performance Indicator (IKU) Achievement in Higher Education - I Ketut Wiriawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Trust among educators constitutes a critical social capital that underpins organizational effectiveness in higher education institutions. This study investigates the impact of trust erosion among educators on the decline in the achievement of Key Performance Indicators (KPIs/IKU) in higher education. The central problem addressed in this research is the weakening of academic collaboration, reduced engagement in the tridharma of higher education, and the emergence of latent conflicts that negatively affect KPI achievement, particularly in lecturer performance, research collaboration, and the implementation of the Merdeka Belajar–Kampus Merdeka (MBKM) policy. This study aims to analyze the relationship between the level of trust among educators and institutional KPI performance, as well as to identify the organizational and social mechanisms underlying this phenomenon. A mixed-methods explanatory design was employed, combining quantitative survey data with in-depth interviews and institutional performance document analysis. The findings reveal a significant negative correlation between trust erosion and KPI achievement. The study concludes that strengthening organizational trust is a strategic prerequisite for sustaining and improving higher education performance.